Corrosion performance of seawater concrete with fly ash under impressed current - Roxas, Cheryl Lyne C. (Animo Repository, 2019)
Corrosion of steel is one of the main causes of failure especially in structures located along coastal areas. This process is electrochemical in nature requiring the presence of oxygen and water in order to occur. In this study, fly ash and seawater were incorporated into the concrete mix to address sustainability in construction materials, which encompasses waste and abundant material utilization. Concrete mix proportions with 15% and 30% fly ash replacement were designed, with freshwater and seawater as mixing and curing medium. Rectangular column specimens with segmented rebars and stainless steel were cast and subjected to impressed current. Results have shown that specimens with fly ash replacement achieved good corrosion resistance. This may have been attributed to the chlorides in seawater which accelerated the hydration process along with the pozzolonic activity of fly ash, thus improving the microstructure and corrosion resistivity of concrete. Seawater increases early strength when used as mixing water but decreases the strength when used as curing medium. The impressed current technique proved to be effective in accelerating the corrosion rate coupled with the use of seawater. © 2019 International Committee of the SCMT conferences. All rights reserved.